A polity study of minority language management in China focusing on Zhuang. Issue 5 (20th October 2019) - Grey, Alexandra
ABSTRACT: This polity study is about the language policy situation in the People's Republic of China (China) with a focus on one official minority language, Zhuang. The paper offers an examination of the language policy and planning (LPP) framework nationally as it relates to official minority languages, and regionally as it relates to the Zhuang minority language. It incorporates technical law and policy data but also data and analysis on the 'sociolinguistic realities "on the ground"' [Freeland, J., & Patrick, D. (2004). Language rights and language survival: Sociolinguistic and sociocultural perspectives. In J. Freeland & D. Patrick (Eds.), Language rights and language survival (pp. 1–33). Manchester: St Jerome Publishing, p. 1]. The paper covers the current sociolinguistic state of Zhuang and its speakers; historical developments in Zhuang language spread, planning and policy; and the central role in Zhuang language management of an official polity, the Zhuangzu, founded to represent Zhuang speakers' interests. The paper is founded on an ethnographically oriented study of interpretations and practices of Zhuang LPP. In analysing the structures and processes of the Zhuang LPP framework, the paper draws out operational limits and policy discontinuities as well as language ideological tensions and other socially situated problems in Zhuang LPP. Many of these will be relevant to LPP studies of other minority languages in China, and potentially elsewhere.